Multi-b value diffusion-weighted magnetic resonance imaging and intravoxel incoherent motion modeling: Differentiation of aggressive lymphoma lesions on initial treatment and activity assessment after chemotherapy. Issue 6 (February 2019) - Liao, Cheng-cheng; Qin, Yun-ying; Tang, Qi; Tan, Xiao-hong; Ke, Qing; Rong, Yan; Zhong, Jian-Hong; Li, Le-qun; Cen, Hong
Abstract : Abstract: The diagnostic efficiency of diffusion-weighted magnetic resonance imaging with different b -values and application of an intravoxel incoherent motion (IVIM) model for differentiating disease states of lymphoma was investigated. Thirty-six patients at initial diagnosis and 69 after chemotherapy underwent diffusion-weighted magnetic resonance imaging (DW-MRI) with multiple b -values. Analysis parameters included the apparent diffusion coefficient (ADC) for each b -value. Standard ADC, D, D *, and f were calculated using an IVIM model. For patients at initial diagnosis, compared with aggressive lymphomas, the benign lymph nodes exhibited higher mean ADC (2.34 vs 0.66 × 10 −3 mm 2 /s, P < .01) for b = 200 s/mm 2 . The AUC, sensitivity, specificity, and the cutoff value were 0.992, 96%, 100%, and 1.09 ×10 −3 mm 2 /s, respectively. For patients who had finished chemotherapy, the f -values of IVIM for those with partial remission (PR) were higher than those of complete remission (CR) (56.22 vs 21.81%, P < .01). The AUC, sensitivity, specificity, and the cutoff value were 0.937, 94%, 82%, 42.10%, respectively. For b = 200 s/mm 2, ADC values are most helpful for characterizing benign lymph nodes and malignant lymphomas. The f -value of the IVIM is most valuable in the identification of residual lesions of lymphomas after chemotherapy.